2017
DOI: 10.1107/s2053229617013183
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxytropylium chloride: the first crystal structure of an unfunctionalized hydroxytropylium ion

Abstract: The crystal structure of hydroxytropylium chloride, CHOH·Cl, the hydrochloride salt of tropone, is described, which represents the first crystallographic characterization of an unfunctionalized hydroxytropylium ion. Crystals were obtained serendipitously from a sample of chlorotropylium chloride after partial hydrolysis. This highlights the role of hydroxytropylium ions as an intermediate in the hydrolytic decomposition of halotropylium halides to tropone. The solid-state structure consists of layers, in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Similarly,t he VT-UV/Vis absorption spectroscopy (Figure 4 bottom)s howedaclear intensification to the absorption peak at 567 nm (characteristic for organic dye Trop-DMA 4b)w hen the temperature increasef rom 10 8Ct o7 08C. Since we used a 1:1r atio of Ph 3 Pa nd Trop-DMA 4b and could only operate our apparatus within the 10-70 8Cr ange, it was not possible to obtain the complete formationo ft he complexes 7b or the complete dissociation to triphenylphosphine and organic dye 4b.This VT-UV/Vis study,however,confirmed the complexation equilibrium and hints that we can potentially use organic dye 4b and its analogues for applications in phosphine sensing and colorimetric analysis of chemical reactions, which Based on our previous works [22b-d] and recent findings from Pçthig and co-workers on crystallographic data of tropylium salts, [28] we believe that the tropylium moiety has differenta ffinities to counterions, especially in the halide series. The ionic charactero ft ropylium halide was observed to increase from chlorides alt to bromide salt.…”
supporting
confidence: 78%
“…Similarly,t he VT-UV/Vis absorption spectroscopy (Figure 4 bottom)s howedaclear intensification to the absorption peak at 567 nm (characteristic for organic dye Trop-DMA 4b)w hen the temperature increasef rom 10 8Ct o7 08C. Since we used a 1:1r atio of Ph 3 Pa nd Trop-DMA 4b and could only operate our apparatus within the 10-70 8Cr ange, it was not possible to obtain the complete formationo ft he complexes 7b or the complete dissociation to triphenylphosphine and organic dye 4b.This VT-UV/Vis study,however,confirmed the complexation equilibrium and hints that we can potentially use organic dye 4b and its analogues for applications in phosphine sensing and colorimetric analysis of chemical reactions, which Based on our previous works [22b-d] and recent findings from Pçthig and co-workers on crystallographic data of tropylium salts, [28] we believe that the tropylium moiety has differenta ffinities to counterions, especially in the halide series. The ionic charactero ft ropylium halide was observed to increase from chlorides alt to bromide salt.…”
supporting
confidence: 78%
“…The electrophilicity of the unsubstituted tropylium ion, as reported by Mayr and co-workers, is comparable to that of tritylium ions stabilized by electron-donating substituents such as a methoxy group. 14 The tropylium ion 15 might therefore be a suitable Lewis acid catalyst with adequate electrophilicity and oxophilicity for the COM reaction. 12 e Gratifyingly, our study demonstrated that the tropylium ion could indeed be used as an organic Lewis acid catalyst to efficiently promote the carbonyl–olefin metathesis reaction with good to excellent outcomes on a broad range of substrates.…”
Section: Introductionmentioning
confidence: 99%